CORRELATION OF TEACHING STYLE WITH LEARNING MOTIVATION WITH INTERVENING MEDIATION OF STUDENT LEARNING ACHIEVEMENT AT ELEMENTARY SCHOOL AT BULAKAN 1 KOTA CILEGON OF THE 2024/2025 ACADEMIC YEAR - Ane Herlina; Andriani Sariwardani; Suandi Silalahi (Cakrawala Pedagogik, 2025)
This study aims to determine the correlation between teachers' teaching styles and students' learning motivation, considering the mediating role of students' academic achievement at Bulakan 1 Elementary School in Cilegon City for the 2024/2025 academic year.This study uses a quantitative approach with a correlational method.The research sample consists of 60 students who were purposively selected.The instruments used included a questionnaire on teacher teaching styles, student learning motivation, and academic achievement data taken from the second semester report cards.Data were analyzed using multiple regression tests and path analysis with the help of SPSS.The research results show that there is a positive and significant correlation between teaching style and student learning motivation.Additionally, academic achievement has proven to be a mediating variable that strengthens the relationship between teaching style and student motivation.Thus, the teacher's teaching style contributes both directly and indirectly to students' learning motivation through the improvement of academic achievement.This research recommends the importance of improving the quality of teaching styles as a strategy to support students' motivation and academic achievement sustainably.